MON-307 Prospective, Longitudinal Study of Glucose-Suppressed GH Levels in 87 Acromegaly Patients with IGF-1 Normalization After Surgical Therapy: Prognostic Value of Nadir GH Levels for Long-Term Remission or Recurrence - Freda, Pamela (J Endocr Soc, 2020)
Surgical removal of the GH-secreting tumor is the initial treatment of choice for acromegaly. Outcome of surgery is assessed by measuring IGF-1 and glucose-suppressed GH levels. IGF-1 normalization is an essential biochemical criterion for remission. The cut-off for nadir GH after oral glucose that signifies remission, however, is debated. It also remains unclear whether GH levels provide additional prognostic or clinically relevant information when IGF-1 results are definitive. To address this question, we examined how initial postoperative glucose-suppressed GH levels change over time on serial testing in patients who achieve initial remission as defined by IGF-1 normalization. We studied 87 acromegaly patients (48M, 39F) who achieved a normal IGF-1 level after surgery alone longitudinally from 1996 to 2019. All had GH measured before and 60, 90 and 120 minutes after 75 or 100 mg oral glucose (OGTT) at ≥ 3 months after surgery and GH and IGF-1 repeated ≥ 1 year later. GH was by measured by sensitive, 22KDa GH specific assays, either a IRMA (DSL, International Reference Standard (IRS) 88/624) or a chemiluminescence immunoassay (IDS-iSYS, IRS 98/574). OGTT Nadir GH levels were also measured in healthy subjects; n=46 (26 M, 20 F, ages 19-71 yr.) by DSL and n=46 (29 M, 17 F; ages 20-66 yr.) by IDS-iSYS. Nadir GH levels in acromegaly patients were compared to the 95%CI of healthy subjects’ mean and categorized relative to healthy subjects’ 97.5 percentile, which was 0.14 µg/L for both assays. IGF-1 levels were compared to age and gender adjusted normal ranges. Subjects were grouped based on initial nadir GH ≤ or > 0.14 µg/L and the patterns of change in nadir GH and IGF-1 at last follow up or until IGF-1 became elevated (i.e. recurrence). Follow up durations are given as median(range). In follow up, 73 patients remained in remission (normal IGF-1) and 14 had a recurrence (elevated IGF-1). Of the 73 in remission, 55 had initial nadir GH ≤ 0.14 µg/L that persisted to 10 yr.(1-22yr.) of follow up, 5 had initial GH ≤ 0.14 µg/L that rose to > 0.14 µg/L by 9(3-21)yr., 10 had GH > 0.14 µg/L that persisted at 5.5(2-22)yr., and 3 had GH > 0.14 µg/L that fell to ≤ 0.14 µg/L at 5(4-7)yr. of follow up. Of the 14 that recurred, 11 had an initial and persistent GH > 0.14 µg/L and developed an elevated IGF-1 level after 6(1-23) yr.. The 3 other patients that recurred had an initial GH ≤ 0.14 µg/L that rose to > 0.14 µg/L by 1-6 years later and subsequently developed an elevated IGF-1 level by 14-16 years of follow up. In summary, we found that the pattern of normal IGF-1 along with nadir GH > 0.14 µg/L on initial testing or developing with time, was associated with recurrence in 14/32 patients. We also found that initial nadir GH ≤ 0.14 µg/L was highly predictive of long-term persistent remission: 60/63 such patients remained in remission. In conclusion, glucose-suppressed GH levels are of prognostic value in acromegaly patients with normal IGF-1 after surgery.